Towards the development of an effective image watermarking system. Issue 2 (22nd November 2021) - Begum, Mahbuba; Uddin, Mohammad Shorif
Abstract: Digital data communication or sharing has increased day by data because of excessive usage of the Internet. It is necessary to protect digital data from unauthorized access. However, it is very difficult to ensure the authenticity of the host data. Digital image watermarking is a significant technology for ensuring this authentication. Existing hybrid domain algorithms are not effective enough to overcome the potential challenges of watermarking techniques. Hence, the current image watermarking technology is devoted toward developing more effective methods with optimization and machine‐learning algorithms for ensuring a better trade‐off among the basic design requirements like imperceptibility, robustness, and capacity simultaneously in addition to security that can be confirmed with lightweight image encryption algorithms. In this research, a framework of standard image watermarking system for ensuring the basic design requirements is given, the existing literature is studied, and the recent trends of image watermarking techniques and their applications are also described to investigate the performance of the state‐of‐the‐art methods along with their limitations. Finally, we have concluded our study by pointing to new research directions.